THE INFLUENCE OF LEARNING STRATEGIES AND STYLES OF THOUGHT ON THE ABILITY OF STUDENTS TO SOLVE ENVIRONMENTAL PROBLEMS - Budiaman Budiaman; Nadiroh Nadiroh (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2015)
This study aims to determine the effect of learning models and styles of thought on the ability of students to solve environmental problems. The study was conducted in SMP 21 Bekasi during August 2012 to May 2013 academic year 2012/2013. This study used an experimental method, with 2 x 2 factorial designs. Variable research include learning model as an independent variable, style of thinking as a control variable, and the ability of students to solve environmental problems as the dependent variable. Sampling techniques using multistage random sampling, a class VIII-2 obtained as an experimental class and class as the control class VIII-1. The results showed that: First, the ability of students to solve environmental problems learning with instructional strategies ekperiensial higher than students using expository. Second, the ability of students to think accommodative style in solving environmental problems is higher than students think assimilative style. Third, the ability of students to solve environmental problems that have accommodative learning style with experiential learning strategies are higher than students who learned with expository learning strategies. Fourth, the ability of students to solve environmental problems that have assimilative learning style with instructional strategies expository higher than students who study with experiential learning strategies.Fifth, the interaction between learning strategy and thinking styles affect students' ability to solve environmental problems. This means that the effect of the interaction between learning strategy and thinking styles affect the level of students' abilities to solve environmental problems. The conclusion of this study is that students are given learning with experiential learning model has the ability to solve environmental problems is higher compared with the gain ekpositori learning.